Akses Air Minum Layak: Apakah Transfer Spesifik dan Tata Kelola itu Penting? - Martino, Yossi; Qibthiyyah, Riatu Mariatul (Jurnal Bina Praja, 2024)
The National Medium-Term Development Plan for 2020-2024 aims to provide 100% of residents with access to safe drinking water. However, according to Central Bureau of Statistics, the average of residents with access to safe drinking water is still at 92% in 2022. Attaining this goal is difficult without focusing on fiscal transfer policy and governance. This study explores the relationship between fiscal transfer and good governance toward access to safe drinking water in each district/city in Indonesia using 2019-2022 data from The Socioeconomics Survey, Central Bureau of Statistics, Ministry of Finance, and Ministry of State Apparatus Utilization and Bureaucratic Reform. The regression of panel data using a fixed effect model shows that specific-purpose capital grants for drinking water and good governance significantly have a positive impact on access to safe drinking water. These results indicate that specific-purpose capital grants still hold a crucial role in providing access to safe drinking water. Meanwhile, good governance is also a key factor in obtaining optimal outcomes in safe drinking water. In the western region of Indonesia, good governance and poor governance have a stronger effect on access to safe drinking water yet specific-purpose capital grant in the eastern region have a higher impact.